Pacemaker Implantation in Patient With Persistent Left Superior Vena Cava and Absent Right Superior Vena Cava - Sabzwari, Syed Rafay Ali (Cureus, 2020)
Persistent left superior vena cava (LSVC) is an asymptomatic congenital heart disease. It is usually found incidentally on imaging, during central line placements or while undergoing electrophysiological procedures. We present a case of a 91-year-old female who initially presented with seizures and was diagnosed with tachy-brady syndrome. She was planned to undergo dual-chamber permanent pacemaker placement. However, during the procedure, she was incidentally found to have an LSVC without a right superior vena cava. Due to challenging anatomy, her pacemaker was changed to a single-chamber atrial lead pacemaker. This case highlights the clinical implications of this unusual structural anomaly, technical difficulties that arise alongside and solutions on how to overcome these issues in the context of pacemaker implantation.